PELOD score, serum procalcitonin, and lactate levels in pediatric sepsis - Jufitriani Ismy; Munar Lubis; Erna Mutiara; Gema Nazri Yani; Yunnie Trisnawati (Indonesian Pediatric Society, 2015)
Background Sepsis remains a major cause of morbidity and mortality among critically ill children in the pediatric intensive care unit (PICU). Procalcitonin and lactate have been used as biomarkers of sepsis, as they have been correlated with disease severity, organ failure and death. The Pediatric Logistic Organ Dysfunction (PELOD) score is a tool to assess the severity of organ dysfunction in critically ill children. Objective To investigate the correlation between PELOD score and procalcitonin and lactate levels in pediatric sepsis. Methods A cross-sectional study was conducted in children with sepsis who were admitted to the PICU from April to July 2012. Sepsis was defined as systemic inflammatory response syndrome (SIRS), as a result of suspected or proven infection. Proven infection was defined as positive culture findings (blood, urine or other specimens) and/or serum procalcitonin >=2 ng/mL. Spearman’s test was used to assess for correlations between PELOD scores and procalcitonin as well as lactate levels. Results Thirty-two patients were analyzed, consisting of 18 males and 14 females with an age range of 1-432 months (median 21 months). There was no statistically significant correlation between procalcitonin level and PELOD score (r=- 0.186, 95%CI -0.502 to 0.174, P=0.308) nor between lactate level(r=-0.069, 95%CI -0.408 to 0.287, P=0.709) and PELOD score. Conclusion Serum procalcitonin and lactate levels are not correlated with PELOD scores in children with sepsis.